2012
DOI: 10.1089/jpm.2012.0034
|View full text |Cite
|
Sign up to set email alerts
|

Associations with the Japanese Population's Preferences for the Place of End-of-Life Care and Their Need for Receiving Health Care Services

Abstract: The present findings may help to develop an effective end-of-life care system in Japan considering Japanese people's need for health care services. Also, the results of this study may underscore the importance of education on receiving home care services especially for the people who presently prefer the hospital for end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The strengths of this study include the investigation of survival time as a primary end-point, and the adjustment for factors influencing prognosis (such as performance status). This study is also the first about this topic in Asian patients who typically prefer hospital rather than home care because of the concern that the latter could shorten their survival [ 11 , 12 ]. Our findings that the home care group had a significantly longer survival than the hospital care group could help to dispel unsubstantiated concerns about the negative effects of home care on patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of this study include the investigation of survival time as a primary end-point, and the adjustment for factors influencing prognosis (such as performance status). This study is also the first about this topic in Asian patients who typically prefer hospital rather than home care because of the concern that the latter could shorten their survival [ 11 , 12 ]. Our findings that the home care group had a significantly longer survival than the hospital care group could help to dispel unsubstantiated concerns about the negative effects of home care on patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Many Japanese people also believe that hospitals provide a higher quality of care than clinics; for example, parenteral hydration is a minimum requirement of hospitals even in patients whose death is imminent [ 11 ]. Patients and their families have often expressed concerns regarding the quality of home care, and many believe that it results in a potentially shorter survival during the terminal stage of cancer compared with hospital care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…End of life care has been a very important issue worldwide. A substantial number of people desire to live and die in their own home (Fukui & Yoshiuchi, ; Gomes, Calanzani, Gysels, Hall, & Higginson, ). Several studies reported that fulfilling the person's wish of dying at home can increase the satisfaction of the patient and their family members (Gomes, Calanzani, Koffman, & Higginson, ; Yao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the reasons why a family would consider themselves unable to provide care while having the patient reside at home include anxieties about what to do when the patients' status worsens and worries that they would not be able to provide sufficient care in the home setting. 22,23 In this study, approximately 40% of respondents felt that the decision was made to use the PCU without having sufficient time for related considerations. Persons forced to investigate PCU admission without knowledge of support services for at-home care and without sufficient time felt that they did not have enough information at the time when they made their decision.…”
Section: (11)mentioning
confidence: 84%